Characteristics Energy, and Protein Intake of Pregnant Women during The Covid-19 Pandemic and Its Relation with Infant Birth Weight - Usman, Fahmil; Salimo, Harsono; Nuhriawangsa, Adi Magna Patriadi (Universitas Airlangga, 2022)
The COVID-19 pandemic is an outbreak that has a risk of a food crisis and changes in diet that have an impact on the nutritional status of pregnant women and babies. This study was aimed to analyze the relationship between the characteristics of pregnant women in the third trimester and food intake during the COVID-19 pandemic with birthweight. This research used cross-sectional method with a sample of 91 third trimester pregnant women at the Pundong and Bantul 1 Community Health Centers, Bantul Regency, Yogyakarta, which were randomly selected. The data was collected using a questionnaire. The nutritional status was measured based on MUAC (Mid Upper Arm Circumference), food consumption was measured using SQFF (Semi-Quantitative Food Frequency) questionnaire, and birth weight was measured using a digital weight scale with an accuracy of 0.1 kg. Bivariate analysis was done using Fisher-Exact with 95% CI. The results showed that the characteristics of pregnant women in the third trimester such as education, income, occupation, and disease history had no relationship with birth weight; gestational age (p = 0.007) and nutritional status (p = 0.002) had a relationship with birth weight; energy intake had no relationship while protein had a relationship with birth weight (p = 0.001). The conclusion is that gestational age, nutritional status, and protein intake have a relationship with birth weight during the COVID-19 pandemic. Therefore, pregnant women should always pay attention to food intake and carry out regular pregnancy checks to health services to detect early abnormalities to prevent low birthweight.